2008
DOI: 10.1007/s10517-008-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhaponticum carthamoides extract on structural and metabolic parameters of erythrocytes in rats with cerebral ischemia

Abstract: Cerebral ischemia in rats was accompanied by an increase in erythrocyte degradation, which results from changes in lipid composition of their membranes. The content of lipids and phospholipid fraction (phosphatidylcholine, sphingomyelin, and phosphatidylserine) decreased, while the relative content of lysophospholipids increased in erythrocyte membranes. The course of treatment with Rhaponticum carthamoides extract (150 mg/kg perorally, 5 days) contributed to an increase in the contents of total lipids and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Upon transplantation, HPDLSCs co-cultured with DFCs grew well and produced root/periodontal ligament-like and periodontal ligament/bone-like tissues. Several studies [36] , [37] have shown that after engraftment, MSCs contribute to tissue repair secretion of trophic molecules, including soluble extracellular matrix glycoproteins, cytokines, and growth factors, and through direct cell-to-cell contact. Moreover, as a type of MSC, DFCs are also young precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upon transplantation, HPDLSCs co-cultured with DFCs grew well and produced root/periodontal ligament-like and periodontal ligament/bone-like tissues. Several studies [36] , [37] have shown that after engraftment, MSCs contribute to tissue repair secretion of trophic molecules, including soluble extracellular matrix glycoproteins, cytokines, and growth factors, and through direct cell-to-cell contact. Moreover, as a type of MSC, DFCs are also young precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of Rhaponticum carthamoides is not associated with serious side effects [ 19 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The intake of Rhaponticum carthamoides is not associated with serious side effects [19,[59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Rhaponticum Carthamoides Extract Increased Muscle Protein Synthesis the Combination Of Rhaponticum Carthamoides Andmentioning
confidence: 99%
“…Their raw materials are most in demand in Russia and abroad. Special attention among them should be paid to valuable MPs R. rosea and R. carthamoides with unique biological activity [12,40,41,[58][59][60][61][62][63][64][65][66][67][68][69]. Both these species are listed in the Red Book of the Russian Federation with the category 'a rare species with resource significance' [70].…”
Section: Resultsmentioning
confidence: 99%